2015
DOI: 10.3389/fpls.2015.00414
|View full text |Cite
|
Sign up to set email alerts
|

Glucosinolate-derived isothiocyanates impact mitochondrial function in fungal cells and elicit an oxidative stress response necessary for growth recovery

Abstract: Glucosinolates are brassicaceous secondary metabolites that have long been considered as chemical shields against pathogen invasion. Isothiocyanates (ITCs), are glucosinolate-breakdown products that have negative effects on the growth of various fungal species. We explored the mechanism by which ITCs could cause fungal cell death using Alternaria brassicicola, a specialist Brassica pathogens, as model organism. Exposure of the fungus to ICTs led to a decreased oxygen consumption rate, intracellular accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 85 publications
2
72
0
Order By: Relevance
“…Furthermore, Quiles et al (2015) investigated the potential of mustard-based botanicals to reduce aflatoxin contamination of wheat tortillas by Aspergillus parasiticus and observed that the gaseous allyl ITC from oriental mustard was more effective than p-HBITC from white mustard; however, substantial reduction in aflatoxin occurred with either treatment. Calmes et al (2015) studied the mechanisms by which ITCs could cause fungal cell death using Alternaria brassicicola as a model organism. The authors demonstrated that exposure to these compounds led to reduced oxygen consumption rate, intracellular accumulation of reactive oxygen species, and mitochondrialmembrane depolarization.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Quiles et al (2015) investigated the potential of mustard-based botanicals to reduce aflatoxin contamination of wheat tortillas by Aspergillus parasiticus and observed that the gaseous allyl ITC from oriental mustard was more effective than p-HBITC from white mustard; however, substantial reduction in aflatoxin occurred with either treatment. Calmes et al (2015) studied the mechanisms by which ITCs could cause fungal cell death using Alternaria brassicicola as a model organism. The authors demonstrated that exposure to these compounds led to reduced oxygen consumption rate, intracellular accumulation of reactive oxygen species, and mitochondrialmembrane depolarization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, isothiocyanates were able to decrease the ATP synthesis in yeast by inhibiting the connection between the electron transport chain and oxidative phosphorylation (Vig et al 2009). Calmes et al (2015) found that isothiocyanates induced oxidative stress in Alternaria brassicicola, a Brassicaceae-specific fungus, decreasing the oxygen consumption rate, increasing intracellular accumulation of ROS and causing mitochondrial-membrane depolarization.…”
Section: Defense Against Biotic Stressmentioning
confidence: 99%
“…Plant-based diets are widely thought to reduce the risk of aging-related diseases (Baenas et al, 2016;Baenas et al, 2017a;Baenas et al, 2017b), which is largely attributed to the activities of their bioactive substances such as polyphenols, vitamin C and other endogenous metabolites (Calmes et al, 2015;Ma et al, 2018;Gillespie et al, 2018). Moreover, plants tend to bring about antioxidant effects owing to the presence of some antioxidant enzymes such as superoxide dismutase (SOD).…”
Section: Introductionmentioning
confidence: 99%